PRINCIPLES OF ARRANGING PHRASEOLOGICAL UNITS IN THE ENTRIES OF RUSSIAN–TURKIC DICTIONARIES (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article presents the principles of arranging phraseological units in the entries of Russian–Turkic dictionaries, illustrated by relevant examples.